Analisis Transparansi Pengelolaan Koin NU Terhadap Minat Infak - Ulum, Makrifatul; Purwanto, Purwanto; Pudail, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research is a descriptive qualitative research. In this study using primary and secondary data sources. Data collection techniques in this study used observation techniques, interviews and 15 documentation from MWC Secang. The object of this research is the Nahdliyin MWC Secang community. Respondents who were questioned in this study were the Chairperson of the MWC and Secang people. The purpose of this research is to complete the literature on transparency in the management of interest in investing through NU coins. Data analysis was carried out using interactive analysis, as we know that transparency is a factor in creating public trust in spending. The results of this study indicate that transparency with the mechanism of openness, the mechanism of public facilities has so far been running well and influencing people's interest in making donations through NU coins at MWC Secang. The public reporting mechanism in detail so far has not run well but matters related to policy in general have been running. So that is the reason why people are interested in making donations through NU coins, especially with the benefits they can experience directly. In this study, management transparency is relevant to influencing interest in making donations through NU coins.